Human occupation and environmental change in the western Maghreb during the Last Glacial Maximum (LGM) and the Late Glacial. New evidence from the Iberomaurusian site Ifri El Baroud (northeast Morocco). (15th September 2019) - Potì, Alessandro; Kehl, Martin; Broich, Manuel; Carrión Marco, Yolanda; Hutterer, Rainer; Jentke, Thalia; Linstädter, Jörg; López-Sáez, José Antonio; Mikdad, Abdeslam; Morales, Jacob; Pérez-Díaz, Sebastián; Portillo, Marta; et al.
Abstract: With the onset of the Last Glacial Maximum (LGM), hunter-gatherers of the so-called Iberomaurusian techno-complex appeared in what is now the Mediterranean Maghreb. During a period of about seven thousand years, these groups left sandy occupation layers in a limited number of archaeological sites, while at the beginning of Greenland Interstadial (GI) 1, the sudden shift towards the deposition of shell-rich sediments and the increase in number of sites document clear changes in subsistence strategies as well as occupation density. It is highly likely that these shifts in human behaviour are related to paleoenvironmental changes in the area, which, so far, are poorly documented in geological and archaeological archives. Ifri El Baroud (Gunpowder Cave, northeast Morocco) contains a well-stratified archaeological sequence covering both phases of Iberomaurusian occupation separated by a sharp sedimentary change. In this paper, new chronological data and detailed investigations on site formation using sedimentology and micromorphology are presented. In addition, results of the analyses of fauna, pollen, macrobotanical remains, and phytoliths are included. This data contributes to a full-scale paleoenvironmental interpretation of the site's archaeological deposits, highlighting the fluctuations of landscape conditions at the transition from the cold-arid Greenland Stadial (GS) 2.1 to the warmer and moister Greenland Interstadial 1. Highlights: The site Ifri El Baroud contains a sequence of early and late Iberomaurusian deposits. The Iberomaurusian sequence spans the interval between roughly 23 ka and 13 ka cal BP. Sedimentological and environmental shifts are recognized. Phytoliths, faunal and macrobotanial remains highlight specific human behaviours.